Az ellenállási jog értelmezése és gyakorlata a Vetus Testamentumban és a Novum Testamentumban - Mészáros, István László (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2024)
This study shows that the right to resist tyranny has deep biblical roots. It derives directly from the biblical principle of the primacy and supremacy of divine and natural law, reflecting universal divine eternal order and justice. From the fact that even public authority is subject to these laws and that, in the event of a conflict with such laws, man-made laws and authority cannot claim obedience. In this case, resistance to them is not only a right but also a conscientious duty. This paper provides a broad outline of the biblical principles that underpin resistance to tyranny. It then describes some of the cases of resistance in the books of the Old and New Testaments which, among many others, have been recurring in the works of the leading authors on the right of resistance throughout European history.